Kenya - Beyond Connections : Energy Access Diagnostic Report Based on the Multi-Tier Framework - Dubey, Sunita (World Bank, Washington, DC, 2021)
Kenya has made great strides in increasing access to electricity to its population. The Multi-Tier Framework (MTF) survey has found about two-thirds of the population of Kenya having access to electricity (either from a grid or an off-grid connection) as of early 2016. Given the high pace of grid and off-grid electrification in the recent years, the MTF provided an updated estimate using extrapolation techniques, which found three-fourths of the population having access to electricity through grid and off-grid options by early 2018. Kenya is well on its way to achieve universal access to electricity much earlier than the Sustainable Energy for All (SEforALL) goal of universal access by 2030. The Kenya National Electrification Strategy (KNES) launched in December 2018 provides a roadmap to achieving the universal electricity access goal by 2022. This initiative includes concerted efforts to increase access to electricity in the fourteen under-served counties through grid, mini-grid, and off-grid options. The present report provides data on energy access from a household perspective that confirm the strategic directions taken by the government in KNES. In addition, it provides additional disaggregated data that can inform implementation of KNES.